Waqf Institutions and Sustainable Development in Nigeria: An Analysis of Community Service Delivery - Adamu Abubakar Muhammad; Adam Muhammad Ardo; Muhammad Bello Adam; Shafa’at Ahmad Aliyu; Zuwaira Jibril Muhammad (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
This study focuses on the contributions Waqf institutions make to community service delivery while critically examining their role in advancing sustainable development in Nigeria. In order to assess the impact of Waqf in sectors including education, healthcare, poverty reduction, and infrastructure development, the study uses both qualitative and quantitative data gathered through surveys, interviews, and document analysis. In order to highlight excellent practices and issues, case studies of prominent Waqf foundations in Nigeria are given, together with their accomplishments and shortcomings. The results show that although Waqf institutions have made important contributions to community service, issues including tax regulatory frameworks, low public awareness, and subpar management techniques have prevented them from reaching their full potential. The report emphasizes that in order to improve the operation of Waqf institutions, legal reforms, capacity training, and public-private collaborations are necessary. With a focus on its alignment with the Sustainable Development Goals (SDGs), the study ends by offering a roadmap for utilizing Waqf as a tool for sustainable development in Nigeria. There are suggestions on how civil society, religious institutions, and government agencies might work together to revive Waqf institutions for efficient community service delivery, which would eventually support social cohesion and national growth.